NILAI KETAKTERATURAN SISI TOTAL PADA GRAF AMALGAMASI SUBDIVISI GRAF DOVETAIL - Nurdini, Eka; Rosyida, Isnaini; Mulyono, Mulyono (Unnes Journal of Mathematics, 2020)
Given a graph G(V,E) with a non-empty set V of vertices and a set E of edges. A total labelling λ:V∪E→{1,2,…,k} is called an edge irregular total labelling if the weight of every edge is distinct. The weight of an edge e, under the total labelling λ, is the sum of label of edge e and all labels of vertices that are incident to e. In other words, w(xy)=λ(xy)+λ(x)+λ(y). The total edge irregularity strength of G, denoted by tes(G) is the minimum k used to label graph G with the edge irregular total labelling. In this paper, authors investigate the total edge irregularity strength of Amalgamation between Subdivision of Dovetail graph with pendant vertices and cycle graph (〖SD〗_n^n,x)*(C_(3n-3),z). The results of this research are tes((〖SD〗_n^n,x)*(C_(3n-3),z))=⌈(9n-3)/3⌉.